South Africa's Stolen Gold: a legal analysis of the impact of illegal mining on South Africas national security - Dyan, Comet Inga (Department of Private Law, 2023)
The proliferation of illegal mining activities in South Africa costs the country's economy an estimated R10 billion a year. Illegal mining activities further jeopardise the future of South Africa's economic development perspective, which is outlined in the National Development Plan (NDP) and highlights the need to eliminate poverty and reduce inequality. Therefore, this posits illegal mining activities as national security threats as they compromise the government's strategic planning programme and directly impact all sectors of security analysis for a modern state: the military, economic, political, social, and environmental sectors. The current fragmented approaches to combat illegal mining activities and the short-sightedness of mining legislation will continue to exacerbate the impact and spread of these activities, from primarily abandoned mines to operational mines. Hence, any real plan to combat illegal mining activities successfully needs a coordinated approach that involves all stakeholders within the mining industry and the security sector, focusing on the key drivers of this highly organised and global illicit economy. In addition, the South African government will need a well thought out policy development strategy that speaks to the future needs of South Africa's mining industry, which may include artisanal mining as a form of an inclusive economic development policy programme. This dissertation briefly explores all the elements mentioned above of South Africa's illegal mining problem. This paper emphasises policy failures and government strategies that have largely ignored the security of the country's mineral resources as they lie on the surface and subsurface of the earth, specifically in abandoned and derelict mines.